Advanced Rietveld refinement and SEM analysis of tobermorite in chemically diverse autoclaved aerated concrete - Schreiner, Jürgen; Götz-Neunhoeffer, Friedlinde; Neubauer, Jürgen; Bergold, Sebastian; Webler, Ralf; Volkmann, Stephan; Jansen, Daniel (Powder Diffraction, 2019)
Changes of structural properties of tobermorite in autoclaved aerated concrete (AAC) for various compositions were characterized and the disadvantages of SEM analysis in this context are discussed. The influence of variations in the chemical composition of raw materials on lattice parameters, morphology and domain sizes of tobermorite was investigated by XRD and for comparison by SEM analysis. Particularly the effect of substitution by Al3+ and (SO4)2− in tobermorite structure was examined. The dimensions of coherently scattering domains were calculated based on the refinement of anisotropic peak broadening of tobermorite in XRD diffractograms using a Rietveld compatible approach. No effect of (SO4)2− on the domain sizes and lattice parameters of tobermorite could be observed. The amount of anhydrite detected by quantitative XRD analysis indicates that all of the available (SO4)2− is present as anhydrite. Lath-like shapes of domains and a larger c parameter are calculated whenever Al3+ is incorporated in a considerable amount. Formation of katoite can be observed very clearly in SEMmicrographs whenever the amount of available Al3+ exceeds a distinct value in the dry mix. The effect of Al3+ and (SO4)2− on tobermorite morphology could not be observed clearly by SEM analysis in AAC samples.<br

Characterization of oxidation protection coatings for high temperature applications by means of nanoindentation and scanning electron microscopy methods - Webler, Ralf; Neumeier, Steffen; Göken, Mathias (Praktische Metallographie, 2014)
Oxidation protection coatings are required for thermally highly stressed components such as turbine blades in aircraft engines Cyclic oxidation experiments were performed on a NiCoCrAlY protective coating of a nickel-based superalloy and hardness and modulus of elasticity (mechanical properties) were determined by nanoindentation before and after the experiments Microstructure and chemical composition were characterized by means of scanning electron microscopy. Here, the focus is on the © Carl Hanser Verla
WW1::988

Evolution of microstructure and mechanical properties of coated Co-base superalloys during heat treatment and thermal exposure - Webler, Ralf; Ziener, Marco; Neumeier, Steffen; Terberger, Philipp J.; Vassen, Robert; Göken, Mathias (Materials Science and Engineering A-Structural Materials Properties Microstructure and Processing, 2015)
WW1::1024
Keywords: High Temperature; Nanomechanics

Isothermal aging of a γ′-strengthened Co-Al-W alloy coated with vacuum plasma-sprayed MCrAlY bond coats - Terberger, Philipp J.; Sebold, Doris; Webler, Ralf; Ziener, Marco; Neumeier, Steffen; Klein, Leonhard; Virtanen, Sannakaisa; Göken, Mathias; Vassen, Robert (Surface & Coatings Technology, 2015)
WW1::1049
Keywords: High Temperature

Local Fracture Toughness and Residual Stress Measurements on NiAl Bond Coats by Micro Cantilever and FIB Based Bar Milling Tests - Göken, Mathias; Webler, Ralf; Krottenthaler, Markus; Neumeier, Steffen; Durst, Karsten (John Wiley and Sons, 2012)
Keywords: Bond coat; Fracture toughness; FIB; Nanoindentation; Micro cantilever; Residual stress; NiAl; Thermal cycling

Local fracture toughness and residual stress measurements on NiAl bond coats by micro cantilever and fib-based bar milling tests - Neumeier, Steffen; Webler, Ralf; Krottenthaler, Markus; Durst, Karsten; Göken, Mathias (12th International Symposium on Superalloys, Superalloys 2012, 2012)
The mechanical behavior of bond coats depends on their chemical composition. Important for the mechanical behavior is the Al content of β-NiAl based coatings. Additionally, internal stresses are present and change during thermal cycling. Therefore bond coats with different Ni and Al content in the as-coated and thermally cycled state are investigated. For the first time, new small scaled methods are used to obtain fracture toughness and internal stresses of real bond coat systems. Micro cantilever bending and stress relaxation tests were performed on a local scale by employing focused ion beam milling. Additionally, the influence of NiAl composition on Young's modulus and hardness is studied by nanoindentation. Results show an increase of Young's modulus with Al content. In off-stoichiometric NiAl a higher hardness and fracture toughness than in binary NiAl is found. The internal stresses change from tensile in as-coated to compressive stresses in thermally cycled bond coats, respectively.
Keywords: Bond coat; FIB; Fracture toughness; Micro cantilever; Nanoindentation; NiAl; Residual stress; Thermal cycling

Microcantilever Fracture Tests of α-Cr Containing NiAl Bond Coats - Gabel, Stefan; Giese, Sven; Webler, Ralf; Neumeier, Steffen; Göken, Mathias (Advanced Engineering Materials, 2022)
MCrAlY bond coats are widely used as oxidation-resistant coatings on superalloys. The major phase is the thermally stable intermetallic β-NiAl phase. The addition of Cr increases the oxidation and corrosion resistance but leads to the formation of α-Cr precipitates. Both phases are brittle and limit the fracture toughness of these coatings. To study the influence of thermal exposure and the resulting changing chemical composition on the fracture properties, the fracture toughness of both phases is measured by notched microcantilever bending, after processing and after oxidation by thermal cycling. The fracture toughness of β-NiAl decreases during thermal cycling due to the depletion in Al, whereas the fracture toughness and the composition of α-Cr stay constant. As the fracture toughness of α-Cr is lower compared with β-NiAl, the formation of α-Cr precipitates is supposed to decrease the fracture toughness of the bond coat.
CRIS-Team Scopus Importer:2022-01-28

On the influence of Al-concentration on the fracture toughness of NiAl: Microcantilever fracture tests and atomistic simulations - Webler, Ralf; Baranova, Polina; Karewar, Shivraj; Möller, Johannes; Neumeier, Steffen; Göken, Mathias; Bitzek, Erik (Acta Materialia, 2022)
While the mechanical properties of the stoichiometric B2 β-phase of NiAl are well established, the effect of off-stoichiometric composition on the fracture behavior has not yet been systematically studied over the entire composition range of 40-55% Al. Here we use microbending tests on notched cantilever beams FIB-milled from NiAl single crystals with an aluminized as well as an oxidation-induced composition gradient to determine the influence of the Al concentration on the fracture toughness. Small variations from the stoichiometric composition are shown to lead to drastic changes in fracture behavior. Ni-rich NiAl shows a gradual decrease of fracture toughness and plastic energy dissipation with Ni-concentration that follows the inverse proportionality to the yield stress postulated by the Ritchie, Knott and Rice (RKR) model. Al-rich NiAl, however, shows a concentration-independent low fracture toughness and no signs of accompanying plasticity - both which can not be described by the RKR model. Detailed atomistic simulations show that rather than affecting the theoretical fracture toughness according to the thermodynamic Griffith criterion, structural vacancies in Al-rich NiAl lower the kinetic barrier for crack propagation, explaining the observed different concentration dependence of the fracture toughness. Similar observations are also expected for fracture in other off-stoichiometric B2 aluminides.
CRIS-Team Scopus Importer:2022-06-10
Keywords: Atomistic simulation; Fracture; Intermetallics; Micro cantilever bending; NiAl